2021
DOI: 10.3390/ijms22158117
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Apoptosis Induced by Dietary δ-Valerobetaine Involves PINK1/Parkin Dependent-Mitophagy and SIRT3

Abstract: Understanding the mechanisms of colorectal cancer progression is crucial in the setting of strategies for its prevention. δ-Valerobetaine (δVB) is an emerging dietary metabolite showing cytotoxic activity in colon cancer cells via autophagy and apoptosis. Here, we aimed to deepen current knowledge on the mechanism of δVB-induced colon cancer cell death by investigating the apoptotic cascade in colorectal adenocarcinoma SW480 and SW620 cells and evaluating the molecular players of mitochondrial dysfunction. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…SIRT3 orchestrates multiple pathways and acts differently in various types of cancer cells, as tumor suppressor but also as tumor promoter [18][19][20][21][22][23][24][25][26]. Intriguingly, in CRC, SIRT3 displays an oncogenic role by deacetylating SHMT2 [27], and acts as tumor suppressor by increasing ROS production and PINK1/Parkin/mitophagy axis activation [9]. Results of this study indicated that whey treatment increased the SIRT3 expression levels in HT-29 and HCT 116 cells.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…SIRT3 orchestrates multiple pathways and acts differently in various types of cancer cells, as tumor suppressor but also as tumor promoter [18][19][20][21][22][23][24][25][26]. Intriguingly, in CRC, SIRT3 displays an oncogenic role by deacetylating SHMT2 [27], and acts as tumor suppressor by increasing ROS production and PINK1/Parkin/mitophagy axis activation [9]. Results of this study indicated that whey treatment increased the SIRT3 expression levels in HT-29 and HCT 116 cells.…”
Section: Discussionmentioning
confidence: 77%
“…The mechanism(s) by which nutrients may affect health span and act as nutritional epigenetic modulators is still not fully understood as it involves multiple evolutionary conserved nutrient-sensing pathways interacting each other, such as sirtuins, conserved key regulators mammalian target of rapamycin, AMP-activated protein kinase, insulin/insulinlike growth factor 1, PINK1/Parkin, and mitophagy [1,2,9]. It is undoubtedly hard to define the exact bioactive component of the 3 kDa whey extract, known to be rich in peptides, betaines, L-carnitine, and acylcarnitines [28], especially in light of the synergism among betaines [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations